The Relation Between Learning Engagement and Academic Self-Efficacy Toward Academic Achievement among University Students - Hong-Ping Pang; Arsaythamby Veloo (Qubahan Academic Journal)
The aim of this study is to investigate the correlation between learning engagement and academic self-efficacy towards academic achievement among normal college students in China. The method of this research is a descriptive survey conducted in the field. Students’ statistical community from Shangrao Normal University in Jiangxi Province, China that their number is about 15,000 people, and 1,507 people were selected as a sample by simple random method. Out of these participants, 471 were malearning engagement (31.3%) and 1036 were femalearning engagement (68.7%) students. This study used Learning Engagement Scale-Student (UWES-S), Academic Self-efficacy Questionnaire (ASEQ) and academic achievement assessment as instruments. The data was analyzed using t-tests, one-way ANOVA and regression analysis. The results indicate that there is no significant gender difference observed in learning engagement or academic self-efficacy. However, when considering different grades, learning engagement demonstrates a significant disparity with the lowest level found among Grade 2 students, which significantly differs from Grade 1, Grade 3, and Grade 4 respectively. On the other hand, no significant differences are observed in academic self-efficacy across different grades. Furthermore, there are notable learning engagement variances between students with varying levels of achievement regarding both learning engagement and academic self-efficacy. Regression analysis reveals that learning engagement directly influences academic achievement while academic self-efficacy acts as a mediating factor for academic achievement. The research results confirmed the significant correlation between students’ learning engagement, academic self-efficacy, and academic achievement; learning engagement has a direct impact on academic achievement, meanwhile academic self-efficacy mediates the relationship between learning engagement and academic achievement. Driven and facilitated by the power of the interactive field, the participants can reduce the sense of inferiority, overcome the fear of feeling and enhance the ability of introspection and self-efficacy.